Loreto Ferrández - Differences in Kinematic and Muscle Activity Associated with ACL Injury Risk in Second Division Female Football Players (Jornada de Jóvenes Investigadores del I3A, 2025)
Differences in Kinematic and Muscle Activity Associated with ACL Injury Risk in Second Division Female Football Players